Using “Cinéma Vérité” (truthful cinema) to facilitate replication and accountability in psychological research† - Suls, Jerry (Frontiers in Psychology, 2013)
To increase replication and accountability, it is proposed that researchers make audio/video recordings of laboratory protocols using currently available technologies, such as smart-phones. A detailed record of the procedure representing each experimental condition of the study design with simulated participants could then be posted on the internet and made accessible to researchers wanting more information about the procedures described in the research publication. Making recordings of all research participants a standard practice would be a greater challenge because of threats to internal validity and ethical concerns, however is feasible and merits a broad discussion among researchers, professional societies, IRB’s and funding organizations.